Influence of inspiratory muscle warm-up exercise on field hockey drag-flick and shooting performance - Avci, N.; Özdal, M.; Vural, M. (European Journal of Physical Education and Sport Science, 2021)
The aim of this study is to examine the effect of inspiratory muscle exercise on drag-flick and shooting performance in hockey. For this purpose, 30 individuals engaged in hockey sports participated in the study as an experimental group. The subjects were applied three inspiratory muscle warm-up exercises (maximal inspiratory pressure, MIP): at 5% intensity (placebo) and 40% intensity (RWU), with 30 breaths x 2 sets and 1 minute rest between sets, first without warming up. After each test, 20 shots drag-flick and 20 shots were performed at the hockey goal, whose scoring was prepared before. The data obtained were analyzed in SPSS 22.0 program. After testing for normality and homogeneity, one-way analysis of variance and LSD correction were performed for repeated measurements. According to the one-way analysis of variance test in repeated measurements; in the drag-flick performance test, a significant difference in favor of the RWU application was observed between the RWU application and placebo and no warming applications (p <0.05). In the shooting performance test, there was a significant difference between RWU application and placebo and no warm-up applications in favor of RWU application (p <0.05). In the drag-flick performance test, when the change of the fatigue scores of the subjects between the applications was examined; there was a significant difference in favor of RWU application (p <0.05). Fatigue was found to be less in RWU application. When the change of fatigue scores between applications in the shooting performance test was examined; there was a significant difference between RWU application and placebo and no warming applications in favor of RWU application (p <0.05). Fatigue was found to be less in RWU application. As a result, it can be said that inspiratory muscle exercise has a positive effect on drag-flick and shooting performance in hockey.